GP194 Periodic fever-the irish PFAPA story so far. (June 2019) - Hawke, Ana Louise; Leahy, Timothy Ronan; MacMahon, Jayne M; MacDermott, Emma Jane; Butler, Karina; Gavin, Patrick; Killeen, Orla G
Abstract : Introduction: Periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) syndrome is the most common autoinflammatory disorder in childhood, with multifactorial, polygenic causes postulated. Objective: To appraise the clinical features, inflammatory characteristics and management of children with PFAPA attending a tertiary Autoinflammatory Clinic. Methods: A retrospective observational chart review of all children with confirmed clinical or suspected PFAPA attending the autoinflammatory clinic at Our Lady's Children's Hospital, Dublin from January 2016. Data were collected on basic demographics, route of referral, symptoms and signs and inflammatory markers during disease episodes (febrile) and non-episodes. Molecular gene analysis if performed, were included. Documentation of all therapeutic agents to date was collated. Results: Thirteen children were identified as having PFAPA. The median age of disease onset was 16 months, (4 months to 4 years). The route of referral was via Immunology (4 patients), Rheumatology (6 patients) and Infectious disease (3 patients). All children presented with episodic, recurrent febrile episodes with associated features. (table 1 ). Median range of duration of episodes was 3–4 days. 69% of patients had documented raised inflammatory markers during a flare, with 84% having high serum amyloid A (SAA) levels, the highest documented being 122 0 mg/l (< 10 normal). Genetic testing in 6 children was negative for other causes of hereditary autoinflammatory disorders. 11 patients had a significant response to an initial trial of corticosteroids, 2 reported rebound flares. Colchicine was the treatment of choice (11), 9 who had a good response. Tonsillectomy was performed in 5 patients, 3 of whom reported benefit. Biologic agents, Anakinra (2) and Adalimumab (1) were instituted in those refractory to colchicine with variable response. Conclusion: This study gives an over view of the burden of disease imposed by PFAPA on an Irish population. All the children presented with fevers, not all had the triad of aphthous stomatitis, pharyngitis and cervical adenitis. The majority of patients had relief of symptoms with an initiation trial of corticosteroid. Colchicine was the most frequently used therapeutic agent to prevent disease flares. Tonsillectomy and biological agents are potential alternative options in some resistant/severe cases.